The Development of a Turbidimetric Method for the Quantitative Determination of Antibiotics of the Aminoglycoside Group in Medications - E. N. Semenova; S. I. Kuleshova; E. I. Sakanyan (Антибиотики и Химиотерапия, 2020)
A method for the quantitative determination of streptomycin sulfate in medicines by the turbidimetric method has been developedand validated. Based on the results of the experiments, it was found that the metrological characteristics of such validation parameters of the method as linearity, precision, and correctness do not exceed the validation criteria. Linearity was noted in the range of streptomycin concentrations from 3.75 to 8.43 μg/ml. The results of validation tests of the method for the quantitative determination of streptomycin indicate the prospects and feasibility of introducing the turbidimetric method into the domestic system for standardization and quality assessment of aminoglycoside antibiotics.